The Importance Of Background Knowledge In Enhance ING Reading Comprehension in SLA (Journal of Pedagogical Inventions and Practices, 2024)
This study explores the impact of background knowledge on reading comprehension among second-year English major students at Shakhrisabz State Pedagogical Institute. The research examines the role of summarization, oral discussions, and comprehension questions in understanding expository and narrative texts. Participants were divided into four groups: two experimental groups engaged in summarization and oral discussions, while two control groups answered comprehension questions. Pre- and post-tests were conducted to evaluate comprehension gains. Findings highlight the critical role of background knowledge, particularly in comprehending expository texts. Summarization improved students' ability to synthesize and integrate information, while oral discussions activated collective knowledge and fostered collaborative schema-building. Narrative texts, with their universal themes, relied less on prior knowledge but still required cultural scaffolding for deeper understanding. The results underscore the importance of pre-reading strategies, schema activation, and tailored instructional approaches to enhance reading comprehension in second-language learners. Implications for teaching practices and curriculum design are also discussed